Innovation, Change and the Intrapreneurial Mindset - John Thompson; Jarna Heinonen; Jonathan M. Scott (Springer, 2022)
Creativity underpins innovation which, in turn, underpins both entrepreneurship and change. Businesses – not ideas or products on their own – generate revenue; and in today’s uncertain world there is a need to commit to ongoing change in these businesses. Much attention has been given to new product development and to process innovation in the ‘corporate world’, but arguably less to the mindset of the intrapreneurial people who are required to drive the change agenda. It is debatable just how seriously organisations seek to identify those people with intrapreneurial attributes and encourage them to identify and seize new opportunities. This chapter examines the role of people in innovation and change, reflects upon relevant aspects of thinking and doing, and offers insight into the ‘intrapreneurial mindset’, which we conceptualise and distinguish from the small firm–oriented entrepreneurial mindset. The chapter offers a framework – based on talent and temperament attributes – for identifying potential intrapreneurs, and it describes how this framework has been used in a small number of large corporate organisations in the United Kingdom. These findings are put into the context of the manager and leader attributes that are more generally sought by many organisations.
Creativity underpins innovation which, in turn, underpins both entrepreneurship and change. Businesses – not ideas or products on their own – generate revenue; and in today’s uncertain world there is a need to commit to ongoing change in these businesses. Much attention has been given to new product development and to process innovation in the ‘corporate world’, but arguably less to the mindset of the intrapreneurial people who are required to drive the change agenda. It is debatable just how seriously organizations seek to identify those people with intrapreneurial attributes and encourage them to identify and seize new opportunities. This chapter examines the role of people in innovation and change, reflects upon relevant aspects of thinking and doing and seeks to offer insight into the ‘intrapreneurial mindset’, which we conceptualize and distinguish from the small firm oriented entrepreneurial mindset. The chapter offers a framework – based on talent and temperament attributes –

for identifying potential intrapreneurs; and it describes how this framework has been used in a small number of large corporate organizations in the United Kingdom (UK). These findings are put into the context of the manager and leader attributes that are more generally sought by many organizations.
Creativity underpins innovation which, in turn, underpins both entrepreneurship and change. Businesses – not ideas or products on their own – generate revenue; and in today’s uncertain world there is a need to commit to ongoing change in these businesses. Much attention has been given to new product development and to process innovation in the ‘corporate world’, but arguably less to the mindset of the intrapreneurial people who are required to drive the change agenda. It is debatable just how seriously organizations seek to identify those people with intrapreneurial attributes and encourage them to identify and seize new opportunities. This chapter examines the role of people in innovation and change, reflects upon relevant aspects of thinking and doing and seeks to offer insight into the ‘intrapreneurial mindset’, which we conceptualize and distinguish from the small firm oriented entrepreneurial mindset. The chapter offers a framework – based on talent and temperament attributes – for identifying potential intrapreneurs; and it describes how this framework has been used in a small number of large corporate organizations in the United Kingdom (UK). These findings are put into the context of the manager and leader attributes that are more generally sought by many organizations.
Workforce Development. Strategies and Practices